ADVERBIA YANG TERBENTUK DARI X + PAR-NI DALAM KALIMAT BAHASA JEPANG - Kurniadi, Ade; rosliana, lina; Ratna, Maharani (Japanese Literature, 2016)
The succession of this thesis is firstly collecting the reference and analyzing thedata. The data’s source of this thesis was gotten by EJJE.WEBLIO.JP,ALC.CO.JP and the other sources that has relation with adverb. The matter thatis discussed in this research is about the structure of adverb formed by adjectivana and noun followed by particle ni.Descriptive method is used in this research. The example of the adverb’s structureformed by noun that followed by particle ni such as, ima ni, ichido ni,isshioukenmei ni and the example of the adverb’s structure formed by adjective nathat followed by particle ni such as jouzu ni, kantan ni, shizuka ni.